Constructing Legitimacy: A Discourse Analysis of Moral Brand Communication - Chen,Shuoyu (2025)
This thesis analyzes how moral brands discursively construct legitimacy and investigates the role of morality in legitimizing brand legitimacy claims and actions. By applying legitimacy theory, the study explores how Patagonia and TOMS Shoes legitimate their moral claims and actions based on discursive legitimation analysis (DLA). Findings showed the frequent and unexpected use of authorization, specifically the B Corp concept, to construct legitimacy, attaching to legitimacy closely. Furthermore, brands consider moral and moral values as a solid foundation to generate legitimate discourse. However, conflicting perspectives of strategic communication operate simultaneously. The moral discourse of brands serves dual strategic purposes, functioning both using communicating morals as one of the branding strategies to promote themselves as legitimate moral organizations. The study approaches the topic of how the brand constructs legitimacy from strategic sides and highlights the complexity and inconsistency of communicating moral and moral values. This thesis contributes to the field of strategic communication by narrowing the knowledge gap within moral brands’ research of strategic communication, offering a new approach to looking at moral brand communication and their strategies to navigate hypocritical challenges.
Keywords: legitimacy; moral brand; discourse analysis; corporate branding; strategic communication